(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2023)
The optimal development strategy for the socio-economic development of Ukraine needs research of specific linkages between natural and socio-economic formations, as well as the research of large-scale and deep-seated violations of the functions of the natural landscapes and their constituents. This also applies to the most resistant to the negative impact of human activity component of the biosphere – the atmosphere and its climatic constituent.